GIANT OSTEOMA IN THE ASCENDING RAMUS OF THE MANDIBLE - RADIOGRAPHIC AND TOMOGRAPHIC ASPECTS OF A CASE - Lísia Daltro Borges Alves; Débora Lima Pereira; Débora Gorito Souto; Jeanne da Cunha Macedo (Portal de Periódicos da Marinha do Brasil, 2024)
Osteoma is an unusual benign tumor of bone origin characterized by proliferation of compact or medullary bone. It is most common in adults between the third and fifth decades of life, with no gender predilection and can be categorized as central, peripheral or extra-skeletal. This study aims to report the case of a patient who was seen at the Odontoclínica Central da Marinha with a final diagnosis of Osteoma with approximately 10 years of evolution. A 58-year-old black woman was referred complaining of pain when chewing on the left side and displacement of the jaw to the right side. On physical examination, facial asymmetry was observed with a well-defined swelling of firm consistency in the parotid region on the left side, in addition to a swollen palate. Radiographically, a rounded and well-defined radiopaque image was observed, affecting the ascending ramus of the mandible, extending to the condyle and coronoid process on the left side. On cone beam computed tomography, a hyperdense, multilobular, well-defined and corticalized image was noted, located on the left side of the mandible, involving the ascending ramus, breaking the lingual cortex and invading the cranial region of soft tissues. The patient underwent an incisional biopsy with a histopathological report compatible with osteoma. Giant osteomas are unusual, mainly in the jaw region. The dentist must be aware of this pathology due to the risk of involvement with syndromes, also because it affects the aesthetics and function of affected patients